2017
DOI: 10.5935/0101-2800.20170040
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease and metabolic syndrome as risk factors for cardiovascular disease in a primary care program

Abstract: In this study involving a population assisted by a primary care program, CKD was confirmed as an independent risk factor for CVD. The presence of MS concurrent with CKD substantially amplified the risk for CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 2 publications
1
3
0
8
Order By: Relevance
“…Among the most frequent comorbidities is SAH 2,4-7 , which in this study was associated with CRF in 70% ( 14) of the individuals, consistent with the constancy already described in the literature 6.7 . In relation to the incidence of DM in the present study, 35% (7) of individuals reported having the disease, being the second most frequently associated comorbidity, as well as previously described in the literature 2,[5][6][7][8]25 . Such information alert to cases of more invasive procedures, taking into account the possible need for control of SAH and the relationship of the DM on the healing repair.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Among the most frequent comorbidities is SAH 2,4-7 , which in this study was associated with CRF in 70% ( 14) of the individuals, consistent with the constancy already described in the literature 6.7 . In relation to the incidence of DM in the present study, 35% (7) of individuals reported having the disease, being the second most frequently associated comorbidity, as well as previously described in the literature 2,[5][6][7][8]25 . Such information alert to cases of more invasive procedures, taking into account the possible need for control of SAH and the relationship of the DM on the healing repair.…”
Section: Discussionsupporting
confidence: 82%
“…Individuals with CRF under HD suffer for years with the disease and its treatment, which leads them to develop various physical, psychological and social problems, directly affecting the quality of life of these, their families, and possibly of society as a whole 5,[20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ancak yapılan çalışmalar çoğunlukla, insülin direnci veya metabolik sendrom varlığı ile birlikte artan BKİ değerlerinin kardiyovasküler riski artırdığını göstermektedir. 72,73 Bunun yanında 43 adet follow-up çalışmanın meta-analiz sonuçları, metabolik olarak sağlıklı kişilerde artan BKİ ile kardiyovasküler riskin de artabileceğini göstermektedir. 74 Dolayısıyla obezite tek başına dahi kardiyovasküler hastalık açısından risk faktörü olarak değerlendirilmektedir.…”
Section: Covid-19 İçin Risk Faktörü Olan Kardiyovasküler Hastalıklarıunclassified